THE EFFECT OF SOCIAL CAPITAL ON THE FOOD SECURITY OF MEMBERS OF THE “MELATI PUTIH” SUSTAINABLE FOOD HOUSE (KRPL) AREA IN BANDUNGREJOSARI, SUKUN DISTRICT, MALANG CITY - Silfi Novita Sari; Sugeng Riyanto; Bayu Adi Kusuma (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2022)
Social capital can affect realizing food security, especially if the household joins an organization or group. One example is KRPL "Melati Putih". The KRPL has the potential that members like and want to learn to grow crops, 85% of members have used their yard and family relations are still well maintained. But, at this time the morale of the members fluctuated because the average member worked. This study aims to identify elements of social capital, identify food security, and analyze the effect of elements of social capital on the food security of KRPL members. The method used is descriptive quantitative with descriptive analysis and PLS-SEM. The results show that social capital in terms of the trust, KRPL members trust the management, Field Agricultural Extension, and other members. In terms of social norms, members obey the activities of regular meetings or meetings, maintenance activities of the Village Nursery, and the use of the yard. In terms of social networks, members help each other, Village Seedlings crops help members meet their food needs, and Field Agricultural Extension can facilitate, provide new information, and provide solutions. Food security of members is good because there is sufficient food supply, easy access to food, and adequate food consumption. Social capital affects the food security of KRPL members. The most dominant element of social capital influencing is trust.